A modular and optimized single marker system for generating Trypanosoma brucei cell lines expressing T7 RNA polymerase and the tetracycline repressor. Issue 2 (February 2012) - Poon, S. K.; Peacock, L.; Gibson, W.; Gull, K.; Kelly, S.
Abstract : Here, we present a simple modular extendable vector system for introducing the T7 RNA polymerase and tetracycline repressor genes into Trypanosoma brucei . This novel system exploits developments in our understanding of gene expression and genome organization to produce a streamlined plasmid optimized for high levels of expression of the introduced transgenes. We demonstrate the utility of this novel system in bloodstream and procyclic forms of Trypanosoma brucei, including the genome strain TREU927/4. We validate these cell lines using a variety of inducible experiments that recapture previously published lethal and non-lethal phenotypes. We further demonstrate the utility of the single marker (SmOx) TREU927/4 cell line for in vivo experiments in the tsetse fly and provide a set of plasmids that enable both whole-fly and salivary gland-specific inducible expression of transgenes.